PROFIL HEMATOLOGI SAPI BALI PADA PERIODA KEBUNTINGAN DI SENTRA PEMBIBITAN SOBANGAN BADUNG - Kendran, Anak Agung Sagung; Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2020)
Bali cattle is germplasm that must be maintained. Various efforts have been made, such as breeding, so that the population can be improved. In the breeding, management of pregnancy will be the main thing to get attention. The gestation period in cattle is an important situation in health management. In this period, physiological status must be in good condition to ensure birth and get calf or calf, which is strong enough and able to survive. Cattle who are pregnant usually tend to weak and vulnerable diseases. This study was conducted to determine the disruption of organs or body functions earlier before showing signs of pain. Blood parameters observed from 28 cows were: The total erythrocytes, the total leukocytes, Packed Cell Volume (PCV), Hb, differential leucocytes (lymphocytes, neutrophils, basophils, eosinophils, and monocytes), Mean Corpuscular Haemoglobine (MCH), Mean Corpuscular Haemoglobine Concentration (MCHC), Mean Corpuscular Volume (MCV). Blood was taken from the jugular vein. The data obtained were analyzed by analysis of variance, with an analytical procedure using the SPSS program. The study results that the hematology of Balinese cattle at each pregnancy phase in Sobangan Badung Breeding Center is not different from non-pregnant cows.